Sistem Pakar Untuk Mendiagnosa Penyakit Infeksi Emerging Dengan Metode Forward Chaining - Yusuf Gunawan; Neni Mulyani; Andi Sapta (Forum Kerjasama Pendidikan Tinggi, 2022)
Emerging Infectious Diseases (PIE) that appear and attack a population for the first time or have existed before but are increasing very rapidly, both in the number of new cases in a population. Its varied structure allows PIE to perform many functions and experience common problems such as the disease in PIE which can be fatal if the symptoms are not immediately recognized. In diagnosing PIE in humans, doctors still use a simple method by observing the symptoms of a patient's PIE so that it takes time to ensure that a patient suffers from PIE so that the patient is always queuing for a consultation. In this case, a media that acts as an expert is needed to help doctors, given the limited knowledge about PIE disease and the lack of counseling staff to conduct socialization of PIE treatment and prevention. The inference model used in making this expert system is forward chaining, while the search technique uses depth first search. Determination in diagnosing expert systems is done through a consultation process between the system and the user. The answer is adjusted to the rules in the system, if the answer is entered according to the applicable rules, the system will provide diagnostic results in the form of information on the PIE disease suffered. With the existence of an expert system with the Forward Chaining method, it can produce a decision on the PIE disease suffered by going through the symptom tracking process with IF-Then logic so that it produces the disease suffered and the solution for its handling